Budaya Lokal Dalam Pemasaran Global Menghadapi Tantangan: Studi Kasus Perusahaan Multinasional Di Asia Tenggara - Ardiansyah, Feri; Mukti Ardiansyah, Wahyu; Zein Saleh, Mohamad (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2025)
Globalization has driven multinational companies to enter Southeast Asian markets, which are known for their diverse cultures, languages, and local values. This study uses a case study approach from companies such as Unilever, McDonald's, and Samsung to examine the cultural challenges that multinational companies face in implementing global marketing strategies in the region. The results show that the success of marketing strategies depends largely on a company's ability to adapt products and communications to local cultural preferences and norms. Key challenges include global corporate culture and local values, cultural misunderstandings of communications, and consumer resistance to single brands. A “glocal” strategy, which combines global strengths with local coordination, has proven to be the most effective approach. This study emphasizes the importance of understanding local culture as a key factor in developing a successful marketing strategy in Southeast Asia.